DESAIN INOVATIF MEDIA PEMBELAJARAN BERBASIS KODULAR DENGAN PENDEKATAN ETNOMATEMATIKA UNTUK MENUNJANG PEMAHAMAN KONSEP MATEMATIKA - Siti Nur Halimah; Eka Farida Fasha (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to create an ethnomathematics-based learning media product using Kodular software. The 4D development paradigm used in this study consists of the following stages: definition, design, development, and dissemination. This study was conducted in class X TSM 1 SMK Al Huda Bumiayu. Questionnaires, interviews, and observations were the methods used to collect data. Media validation questionnaires, material validation questionnaires, and student response questionnaires (practicality) were the tools used in this study. Practicality and product validity tests were used as data analysis methods. According to the research findings, the practicality test using the student response questionnaire produced a percentage of 90.0% with a very practical category, the validation test on the media or construct showed a final percentage of 98% with a very valid category, and the validation test on the content or material obtained a final percentage of 94% with a very valid category. Thus, it can be said that the creation of Kodular-based learning materials is valid and practical. Based on the research, students' understanding of mathematical concepts can be supported and the learning process is assisted by this Kodular-based learning resource.